Once More About Origin of Birds and Flight: “Cursorial” or “Arboreal”? - Bogdanovich, A.I. (Вестник зоологии, 2007)
Despite the long-time history of studies of origin and early evolution of the birds, some issues remain open. One of them is the evolutional reasons for the hallux reversion in the bird foot. Some functional sequences of such hallux orientation and its possible importance in evolution of birds are shown. In our opinion, the functional universalism of the anisodactyl foot with well-developed, low placed and opposable hallux allows to unit, in certain sense, the theories of “arboreal” and “terrestrial” origin of birds and flight.